Modified Biopsy Assessment for Endobronchial Ultrasound in Diagnosis of Peripheral Lung Neoplasms - E. A. Pushkarev; A. V. Vazhenin; K. I. Kulaev; I. M. Yusupov; K. S. Zuikov; I. A. Popova; A. S. Kazantsev (Креативная хирургия и онкология, 2022)
Background. Diagnosis and treatment of malignant lung neoplasms are pressing issues. Peripheral lung cancer verification rate with endobronchial ultrasound varies within 30–85 %.Aim. To advance endobronchial ultrasound precision, a modified biopsy technique has been developed and introduced into clinical practice at the Chelyabinsk Regional Clinical Centre for Oncology and Nuclear Medicine. The modification comprises real-time ultrasound image guidance of the biopsy forceps alignment and opening. The technique patent for invention is RU 2719666 C1.Materials and methods. Modified endobronchial ultrasound has been performed in 66 patients with suspected peripheral lung malignancy at the Centre’s Department of Endoscopy within 2019–2021. Bioptic material was delivered for histological and, when necessary, immunohistochemical examination.Results. Malignancy diagnosis was verified in 78.8 % cases. The modified technique is relatively safe, with complications detected in two patients (3.8 % cases) and managed conservatively with success. Discussion. The standard biopsy technique provided for a lung malignancy verification rate of 57.7 % over 2019–2021. Thus, the rate improvement by modified technique is 21.1 %. The modified technique is relatively safe, with complications reported in two patients (3.8 % cases) and managed conservatively with success. Modified endobronchial ultrasound was adequately tolerated, with no increase in patient examination time. The technique can supersede more invasive diagnostic procedures.Conclusion. We believe that the modified technique will improve the power of endobronchial ultrasound, reduce examination time and expedite prescription of special therapies.